100 years of Australian Antarctic expeditions - Australia. Department of Sustainability, Environment, Water, Population and Communities. Australian Antartic Division (Kingston, Tas. : Australian Antartic Division, 2011)
"The Centenary website has been created for the centenary of the 1911-1914 Australasian Antarctic Expedition, led by Douglas Mawson, to commemorate 100 years of Australian Antarctic Expeditions."
Title from title screen (viewed on 18 Aug. 2011)
Text, graphics.
Mode of access: Internet via World Wide Web. Available at: http://centenary.antarctica.gov.au
Selected for archiving
Keywords: Mawson, Douglas, -- Sir, -- 1882-1958 -- Travel -- Antarctica; Antarctica -- Discovery and exploration -- Australian